Efeito da estimulação elétrica sob a reinervação de músculos desnervados em ratos - Pinheiro, Clara Maria (Universidade Federal de São Carlos, 2016)
Peripheral nerve injury disrupts the normal functions of neurons and leads to rapid and progressive alterations in structural skeletal muscle, such as muscle atrophy and fibrosis, causing functional deficits. Electrical stimulation (ES) has been recommended to treat denervated muscles. The best parameters of ES to minimize muscle atrophy due to denervation is controversial. Furthermore, it is not clear if ES can, in fact, affect reinnervation of denervated muscles. Thus, this thesis has two main objectives: 1) to verify if ES, applied to denervated muscles by surface electrodes, can affect neuromuscular recovery after nerve crush injury in rats; and 2) to assess the impact of ES on fibrosis establishment in denervated muscles. Two manuscripts were produced and used the same experimental groups. Thirtyfive Wistar rats were divided into 5 groups: (1) Normal (N); (2) 7-day denervation (D7d); (3) 7-day denervation and ES (DES7d); (4) 15-day denervation (D15d); and (5) 15-day denervation and ES (DES15d). Tibialis anterior (TA) muscle denervation was induced by crushing the sciatic nerve. The ES protocol to stimulate TA muscles consisted of: 200 contractions per day divided into 4 consecutive series of 50 contractions, with 10-minute rests between each set. The following parameters were used: exponential monophasic pulse; width time: 2x chronaxie; amplitude: motor level; time On: 3s and Off: 6s. The sciatic functional index was calculated. Muscle excitability was assessed considering the rheobasis, chonaxie and accommodation. Morphometric analyses, such as the muscle fiber cross-sectional area and percentage of connective tissue proliferation were used to characterize muscle morphology. Molecular markers related to reinnervation (neural cell adhesion molecule, NCAM), neuromuscular junction organization and maintenance (MuSK, Dok-7 and nicotinic Acetylcholine Receptors (nAChR) subunits), muscle mass control (atrogin-1, MuRF1, myoD and myostatin), fibrosis (TGF-β and myostatin), extracellular matrix remodeling (metaloproteinases, MMPs) and inflammation (TWEAK/Fn14) were investigated by molecular biology techniques such as western-blot, qPCR or zymography. The main results showed ES impaired natural recovery of denervated muscles accentuating disability, muscle atrophy and fibrosis, as well as reducing muscle excitability. These morphofunctional and electrophysiological changes were related to different modulations of all molecular markers investigated in a timely manner. Overall, this thesis provides evidence that ES can delay the reinnervation process by modulating factors related to NMJ stability and organization, as well as induced disability and muscle atrophy, and decreased muscle excitability. In addition, ES applied to denervated muscles induced muscle fibrosis by modulating inflammatory pathways and also extracellular matrix production and remodeling. Warnings should be given to rehabilitation teams when recommending ES to treat denervated muscles.
Keywords: Estimulação elétrica; Metaloproteinase; Fibrose e inflamação; Electrical stimulation; Metalloproteinase; Fibrosis e inflammation; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL